THE HEAD MASTER’S POLICIES IN FULFILLING THE REQUIRED INFRASTRUCTURE FACILITIES OF THE STATE ISLAMIC HIGH SCHOOL (MAN) OF DOLOK MASIHUL SERDANG BEDAGAI REGENCY - Mahyuni Mahyuni (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
. The purpose of this study was to determine the Head Master’s Policy formulation to meet the infrastructure needed by MAN Dolok Masihul Serdang Bedagai regecy, Implementation of Head Master’s Policy Fulfills the Infrastructure Facilities Required by MAN Dolok Masihul Serdang Bedagai regency, and Evaluation of Head Master’s Policy to meet the Required Infrastructure Facilities. This research uses descriptive qualitative research. Data in this study were obtained through observation, interviews, data collection and documentation. The data collected is analyzed and described so that it is easier to understand and can make conclusions. Test the validity of the data used through four stages namely, trust (credibility), transferability, dependability, and confirmability. The results of this study indicate that the Head of Madrasa makes policy formulations in fulfilling infrastructure facilities in MAN Dolok Masihul Serdang Bedagai Regency using programs or deliberations. Head of Madrasah in implementing the Head of Madrasah policy meets the infrastructure by paying attention or monitoring of what is born at the time of policy formulation. Head MasterPolicy Evaluation Meets Infrastructure Needed by MAN Dolok Masihul Serdang Bedagai Regency is done by direct monitoring by the Head Master himself. The results of evaluations carried out that, often hampered in completing the required infrastructure. Keywords: Head Master’s Policies, Facilities and Infrastructure